Medieval Africa, 1250-1800 - Oliver, Roland Anthony (Cambridge University, 2013)
A radically revised version of The African Middle Ages 1400-1800, and the companion volume to the authors' well-known Africa since 1800 (now in its fourth edition). It takes African history from about 1250 AD to the period of early European contact from the 15th century onwards. It will be useful for introductory courses in colleges and universities.